SURVIVAL RATE Wallago lerri THE TRANSPORT SYSTEM IS COVERED WITH DIFFERENT DENSITY - Yongki Hendra; Usman M Tang; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Wallago lerri is one of fresh water fish that it has value economical high that it isinteresting to in cultivation. Prior to the business of cultivating beforehand donebusiness domestication. The first step in domesticated is transportingtransportation fish to place the location of domestication. This research aimed atdetermining the influence of solid stocking different against Survival rates, fish insize 12-19 cm carting a closed system during two-three hours and knowing thedensity of the best. This research using design random complete treatment densitythat is, with 3 p1 10/5 litres, the tail p2 15 / 5 litres of and p3 20 / 5 litres, the taileach treatment in repeated three times. The data in extract Survival rates andwater quality. The result showed that the density of that has been tested don ' tgive the influence of real ( P > 0.05 ) against Survival rates. Survival rates eachtreatment P1 90 %, p2 88.6 % and p3 88.3 %, so that treatment are consideredeitherKey Words : Wallago lerri, Surviva rate, Transporting, Density